"Análisis económico de la producción y propagación de plantas clonales de cacao (Theobroma cacao L.) por el método de ramilla vs injerto de tipo nacional". - Zambrano Cueva, Maritza Alexandra (2014)
Cocoa (Theobroma cacao L) represents the third largest agricultural export of Ecuador and is a source of income for more than 100,000 small family cocoa farmers in 26 provinces of Ecuador, with approximately 470,000 ha, within which stand the Guayas, Los Rios, Manabí, El Oro, Esmeraldas, Bolivar, Pichincha. (Quiroz, 2012) Excellent quality, delicate floral aroma and delicious taste "Up" are two of the features that have catapulted the "National" cacao as the best in the world is for this reason that cocoa production in the country has become one of the most important factors for agricultural exports. Currently, there is a need to renew and rehabilitate more than 50% of the existing area with improved materials, with high levels of production and adaptation to different environmental conditions, as well as possessing characteristics of aroma and flavor. To meet this end in the country basically employs two techniques vegetative or asexual propagation: By grafting and twigs through which lNlAP and some companies or individuals producing, propagating material of cocoa type National..................................................................